1998
DOI: 10.1172/jci2496
|View full text |Cite
|
Sign up to set email alerts
|

A selective human beta3 adrenergic receptor agonist increases metabolic rate in rhesus monkeys.

Abstract: Activation of ␤ 3 adrenergic receptors on the surface of adipocytes leads to increases in intracellular cAMP and stimulation of lipolysis. In brown adipose tissue, this serves to upregulate and activate the mitochondrial uncoupling protein 1, which mediates a proton conductance pathway that uncouples oxidative phosphorylation, leading to a net increase in energy expenditure. While chronic treatment with ␤ 3 agonists in nonprimate species leads to uncoupling protein 1 up-regulation and weight loss, the relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(50 citation statements)
references
References 24 publications
(21 reference statements)
1
49
0
Order By: Relevance
“…In rodents [68,69], dogs [70] and rhesus monkeys [71] 3-adrenoceptor agonists not only activate thermogenesis but, when given repeatedly, they increase the capacity of brown fat to respond to acute activation. Moreover, in phaeochromocytoma, an adrenal medulla neuroendocrine tumour, over-secretion of noradrenaline and adrenaline causes a marked increase in brown adipose tissue mass in humans, associated with reduced body fat content [72,73].…”
Section: Brown Adipose Tissuementioning
confidence: 99%
“…In rodents [68,69], dogs [70] and rhesus monkeys [71] 3-adrenoceptor agonists not only activate thermogenesis but, when given repeatedly, they increase the capacity of brown fat to respond to acute activation. Moreover, in phaeochromocytoma, an adrenal medulla neuroendocrine tumour, over-secretion of noradrenaline and adrenaline causes a marked increase in brown adipose tissue mass in humans, associated with reduced body fat content [72,73].…”
Section: Brown Adipose Tissuementioning
confidence: 99%
“…Also, UCP-1 levels in the monkeys increased after 2-and 4-weeks of treatment (3 mg/kg, iv, twice a day). 53 The effects are expected to be similar in humans.…”
Section: ß 3 -Adrenergic Receptor Agonistsmentioning
confidence: 99%
“…Recently, a novel human ß 3 -AR agonist, 4-(3-hexyl-ureido)-N-(4-{2-[(S)-2-hydroxy-phenoxy)-propylamino]-ethyl}-phenyl)-benzenesulfonamide (L-755507), a potent and selective partial agonist, has been shown to mediate lipolysis and increase uncoupling protein-1 and metabolic rate in rhesus monkeys. 53 L-755507 exhibited an EC 50 of 0.45 nM in Chinese hamster ovary cells expressing the human ß 3 -AR with an intrinsic activity of 52% that of isoproterenol. This drug was a thousand-fold selective for the human ß 3 -AR compared with the human ß 1 -AR (EC 50 = 580 nM, intrinsic activity = 25%), with no agonist activity on cells expressing the human ß 2 -AR.…”
Section: ß 3 -Adrenergic Receptor Agonistsmentioning
confidence: 99%
“…In rats, this increase is reflected in thermogenesis and weight loss due to a decrease in body lipid with no loss in muscle mass (Arch et al, 1990). Recently, it was demonstrated that chronic treatment of monkeys with selective human ␤ 3 -adrenergic receptor agonists elicits lipolysis and metabolic rate elevation (Fisher et al, 1998;Hom et al, 2001). Thus, ␤ 3 -adrenergic receptor agonists might be useful for the treatment of obesity in humans.…”
Section: Ethyl]amino]ethyl]phenyl]-4-[4-[4-(trifluoromethyl)phenyl]thmentioning
confidence: 99%